RELATIONSHIP OF HUSBAND SUPPORT WITH BREASTFEEDING BEHAVIOR IN HEALTH WORK AREA AMBON MALUKU BIG WATER - Nuke Chesti; Agus Aan Adriansyah; Mursyidul Ibad; Novera Herdiani (UNUSA Press, 2022)
The coverage of exclusive breastfeeding is still an important problem in Indonesia because the fulfilment of nutritional needs is very necessary for all humans, especially infants. Meeting the nutriotional needs of infants can be obtained from exclusive breastfeeding. The success of exclusive breastfeeding in influenced by many factors, one of which is husband’s support and breastfeeding behaviour. This study aims to analyze the relationship between husband’s support and breastfedding behaviour in the Work Area of the Air Besar Health Center, Ambon, Maluku.. This research is an analytic observational quantitative research with a cross sectional approach. The sample size in this study was 36 breastfeeding mothers. The variables in this study are husband's support and breastfeeding behavior. The sampling technique used was simple random sampling and used the Pearson correlation test as a data analysis technique. This study uses primary data obtained from questionnaires and secondary data from the records of the Air Besar Ambon Maluku Health Center. The results showed that almost all respondents received support from their husbands (86.1%) and almost all respondents carried out breastfeeding behavior (80.6%). The results of the Pearson correlation test for the relationship between husband's support and breastfeeding behavior have a significance value of 0.000 < 0.005, which means that there is a relationship between husband's support and breastfeeding behavior. Pearson correlation value of 0.817 indicates a very strong relationship. The conclusions in this study indicate that husband's support has a very strong relationship with the success of breastfeeding behavior in the Air Besar Ambon Health Center Work Area. The better the support provided by the husband to his wife, the higher the number of breastfeeding behavior will be. It is hoped that the puskesmas can provide assistance to married couples to explain the importance of husband's support for the success of breastfeeding behavior.